Evaluasi Program dan Teknologi Kinerja dalam Pembelajaran - Nasril Nasril (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2026)
The world of education currently faces a major challenge in aligning technology investments with tangible improvements in learning outcomes. This study aims to evaluate the effectiveness of learning programs from a performance technology perspective to bridge achievement gaps through integrated interventions. The main issue discussed is the gap between extensive content digitization and actual performance outcomes, where technology often functions only as an administrative tool without directly improving competencies. This study employed a literature review method using systematic content analysis of scientific publications from the past ten years. The findings indicate that learning program evaluation based on performance technology functions as a quality control instrument by measuring achievement through measurable indicators, including subject mastery and learning time efficiency. However, implementation still encounters various challenges, such as fragmented technology systems and limited analytical skills among educators. This study offers an original framework that positions technology as a performance driver to minimize learning process errors. In conclusion, optimizing learning can be achieved through the integration of systematic evaluation and appropriate technology utilization to support sustainable human development.